Environmentally sustainable cooling strategies in milling of SA516: Effects on surface integrity of dry, flood and MQL machining. (15th March 2021) - Race, Adam; Zwierzak, Iwona; Secker, Jack; Walsh, Jonathan; Carrell, Julia; Slatter, Tom; Maurotto, Agostino
Abstract: The recent move towards 'Environmentally Sustainable Manufacturing' (ESM) is leading heavy industries (e.g. oil & gas, nuclear) to explore low-impact manufacturing strategies. In machining, however, most processes are still performed using traditional cooling method using flood or high pressure lubricant emulsions. These emulsions are expensive in their maintenance and disposal, and present a significant environmental concern. This novel study combines evaluations of the performance of low-impact cooling strategies, such as dry milling or minimum quantity lubrication (MQL), in the manufacture of an industrially important pressure vessel carbon steel (SA516) using coated carbide inserts. Tool wear, surface roughness, residual stress and energy consumption were measured during metal cutting trials for each strategy and then compared. Likely tool wear performance when using candidate lubricants was screened prior to machining trials using standard tribological high frequency reciprocating tests. Significant improvements in surface integrity and tool wear were observed when machining with dry and MQL when compared with traditional flood coolant. Measured energy footprints for dry and MQL were also lower when compared to flood coolant machining providing cost savings and environmental advantages in manufacturing using ESM approaches.